Religious authority in the Spanish Renaissance - Homza, Lu Ann, 1958- (Johns Hopkins University studies in historical and political science, 2000)
In Religious Authority in the Spanish Renaissance, Lu Ann Homza rejects the traditional view of the Spanish Renaissance as a battle of strict opposites in favor of a more nuanced history. Through analyses of Inquisition trials, biblical translations, treatises on witchcraft, and tracts on the episcopate and penance, Homza illuminates the intellectual autonomy and energy of Spain's ecclesiastics, exploring the flexibility and inconsistency in their preferences for humanism or scholasticism, preferences which have long been thought to be steadfast.